PERANCANGAN DAN PEMBUATAN SISTEM INFORMASI AKUNTANSI PADA PT.LUMAJANG JAYA SEJAHTERA - Rionaldo - Wibowo; Djoni Haryadi Setiabudi; Gregorius Satia Budhi (Jurnal Infra, 2014)
Nowdays, registration, journalizing, and creating report system at PT. Lumajang Jaya Sejahtera still use the old methods or traditional way such as document word. Accounting which is doing manually, can enhance the risk of error calculation at creating journal. And regular data storage didn’t exist yet, it causes the important data is easy to lose. Based on the background of the problem, accounting information will be designed with system which has been computering so that can decrease the error in calculation. The result which is gotten from application that has been made, are saving lease data, selling data and also supplier-customer data.Before creating the program, must do analyzing company, then proceed with the design of the program. Analysis performed directly on the company concerned. The process of its using software VB.net and SQL server.